2020
DOI: 10.1002/ange.201914335
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Palladium Hydride for Electrocatalytic N2 Reduction under Ambient Conditions

Abstract: The electrocatalytic nitrogen reduction reaction (NRR) is an alternative eco‐friendly strategy for sustainable N2 fixation with renewable energy. However, NRR suffers from sluggish kinetics owing to difficult N2 adsorption and N≡N cleavage. Now, nanoporous palladium hydride is reported as electrocatalyst for electrochemical N2 reduction under ambient conditions, achieving a high ammonia yield rate of 20.4 μg h−1 mg−1 with a Faradaic efficiency of 43.6 % at low overpotential of 150 mV. Isotopic hydrogen labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
(23 reference statements)
0
28
0
Order By: Relevance
“…Although the synthesis of NH 3 from N 2 and H 2 is exothermic under standard conditions, NRR is kinetically sluggish and contains complex multistep owing to difficult N 2 adsorption and NN cleavage. [170,171] Designing novel electrocatalysts by lowering the N 2 reduction energy has been explored to surmount the energy barriers. Recently, DES (PEG 200/ thiourea)-derived Fe 3 S 4 nanosheets were solvothermally prepared to use as an NRR electrocatalyst.…”
Section: Other Electrocatalytic Reactionsmentioning
confidence: 99%
“…Although the synthesis of NH 3 from N 2 and H 2 is exothermic under standard conditions, NRR is kinetically sluggish and contains complex multistep owing to difficult N 2 adsorption and NN cleavage. [170,171] Designing novel electrocatalysts by lowering the N 2 reduction energy has been explored to surmount the energy barriers. Recently, DES (PEG 200/ thiourea)-derived Fe 3 S 4 nanosheets were solvothermally prepared to use as an NRR electrocatalyst.…”
Section: Other Electrocatalytic Reactionsmentioning
confidence: 99%
“…43.60% efficiency with 20.40 µg h −1 mg cat −1 was achieved. [205] In situ studies and DFT calculations revealed that unique NRR reaction mechanism which differs in protonation step played vital role in improving the efficiency.…”
Section: (22 Of 44)mentioning
confidence: 99%
“…Notably, Pt‐based catalysts of ECSA can be determined via the H adsorption‐desorption from CV curves [22] . Pd‐based catalysts of ECSA can be calculated by the reduction charge of PdO reduction peak from CV curves [21b] . Although each catalyst with different preparation method, catalyst loadings and morphology, will lead to different catalytic ability of NRR in the previous reports, the electrochemical results (the current densities, NH 3 yield rates) can be normalized to the ECSA to exclude the effects of different catalysts, allowing for a fair comparison.…”
Section: Basic Understanding Of Nrrmentioning
confidence: 99%
“…As described above, α ‐PdH formation during electrochemical process can improve the catalytic performance through a hydride migration mechanism. Based on this premise, nanoporous palladium hydride were prepared by a dealloying method and used as an excellent electro‐catalyst for NRR with the NH 3 formation rates of 20.4 mg h −1 mg cat −1 and FEs of 43.6% [21b] . They also used isotopic tracer methods to understand the mechanism of NRR on nanoporous‐PdH 0.43 .…”
Section: Nrr On Noble Metal (Viii) Catalystsmentioning
confidence: 99%
See 1 more Smart Citation